I shouldn't even be doing this [large type] : and other things that strike me as funny - Newhart, Bob (Hyperion, 2006)
The legendary comedian shares a collection of anecdotes from throughout his life and entertainment career, as well as humorous observations on life, television, golf, family holidays, drinking, his beginnings as an accountant, and other topics.